Legal Analysis of The Enforcement of Article 18 of The Regulation Issued by The Director General of Taxes, Numbered PER-03/PJ/2022, Regarding Tax Invoices - Ban Hin, Siaw; Markoni; Nardiman; Widarto, Joko (Jurnal Legisci, 2024)
The Republic of Indonesia implemented Law Number 12 of 2011, explicitly establishing rules and regulations. Law Number 13 of 2022 has since revised this law. This Law enhances the current legislation, precisely Law Number 10 of 2004. Law Number 12 of 2011 prescribes the procedure for enacting laws and establishes guidelines for resolving conflicts or inconsistencies between these laws and regulations. The objective of this study is to analyze the legal effectiveness of Article 18 of Regulation PER-03/PJ/2022, which was issued by the Director General of Taxes, to Law Number 7 of 2021 on the Harmonization of Tax Regulations and Constitutional Court Decision Number 91/PUU-XVIII/2020. This research methodology entails examining values, norms, and written regulations, establishing a solid connection to the normative legal aspects of the library. The research has determined that the Regulation of the Director General of Taxes Number Per-03/PJ/2022 regulates Tax Invoices and has exceeded its authority in issuing Tax Invoices. The aforementioned rule pertains to the regulatory framework established by the Minister of Finance, which governs this particular matter and confers jurisdiction upon the director general of taxation. The Regulation of the Director General of Taxes Number 03/PJ/2022, which concerns Tax Invoices, does not possess enforceable legal authority and is open to scrutiny by the Supreme Court. Legal certainty is paramount as it provides taxpayers with a lucid and all-encompassing comprehension of their rights and obligations.